2013
DOI: 10.1177/1049731513477214
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Chinese Virtues Questionnaire

Abstract: Objectives: The present study examined the psychometric properties of the Chinese Virtues Questionnaire (CVQ). The reliability, factor structure, construct validity, and temporal stability of the inventory were examined. Method: A university student sample (n ¼ 878) and a working adult sample (n ¼ 153) were recruited. Participants were asked to complete the paper-and-pencil CVQ and a set of questionnaires to measure both their positive and negative psychological status. Results: The results supported the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 52 publications
6
62
1
1
Order By: Relevance
“…Recently, Duan et al (2012) adopted the combined emic-etic approach to select items with functional equivalence and conceptual equivalence in the quantitative and qualitative analyses, which resulted in a three-dimensional strengths model (i.e., relationship, vitality, and conscientiousness). The follow-up studies have demonstrated sound psychometric properties of the revised questionnaire (Duan et al 2013;Zhang et al 2014). Recently, from the perspectives of psychology and culture, McGrath (2015) adopted different inventories and 1,070,549 samples to explore the structure of strengths and virtues, and likewise revealed the same three-factor structure (i.e., caring, inquisitiveness, and self-control).…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Duan et al (2012) adopted the combined emic-etic approach to select items with functional equivalence and conceptual equivalence in the quantitative and qualitative analyses, which resulted in a three-dimensional strengths model (i.e., relationship, vitality, and conscientiousness). The follow-up studies have demonstrated sound psychometric properties of the revised questionnaire (Duan et al 2013;Zhang et al 2014). Recently, from the perspectives of psychology and culture, McGrath (2015) adopted different inventories and 1,070,549 samples to explore the structure of strengths and virtues, and likewise revealed the same three-factor structure (i.e., caring, inquisitiveness, and self-control).…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 97%
“…A brief instrument with good psychometric characteristics is thus required to measure the three kinds of strengths for clinical populations (Duan et al 2012(Duan et al , 2013. Accordingly, they created a 12-item Brief Strengths Scale (BSS) (Ho et al 2016) for assessing temperance strength, intellectual strength, and interpersonal strengths.…”
Section: Relationship Between Demographic Variables and Strengthsmentioning
confidence: 99%
“…Confirmatory factor analysis and psychometric evaluation suggested 3 well-established and culturally meaningful virtues, namely, relationship, vitality, and conscientiousness. 27 Relationship reflects the positive cognitions, emotions, and behaviors (ie, kindness, teamwork, fairness, love and being loved, authenticity, leadership, forgiveness, and gratitude) of interacting with other people; it manifests as an affinity in the process of interpersonal relationships. Vitality reflects the positive qualities to the world/society, such as humor, curiosity, zest, creativity, perspective, hope, social intelligence, beauty, bravery, and belief; it manifests as the vigorousness in the process of social environment and social relationships.…”
mentioning
confidence: 99%
“…All these validations have consistently found a one factor structure explaining between 44% (France) and 73.1% (Japan) of the variance. Convergent validity has been tested using instruments including the Subjective Happiness Scale (Lyubomirsky and Lepper 1999), Satisfaction with Life Scale (Diener et al 1985), Revised Life Orientation Test (R-LOT) (Scheier et al 1994), Positive and Negative Affect Schedule (Watson et al 1988), Chinese Virtues Questionnaire (Duan et al 2013) and Brief Symptom Inventory (Wang et al 2013). Convergent validity correlations with the above mentioned scales ranged from .21 to .68 all of them being statistically significant.…”
Section: Introductionmentioning
confidence: 99%